2017
DOI: 10.1080/13880209.2017.1302485
|View full text |Cite
|
Sign up to set email alerts
|

Methanol extract of Nigella sativa seed induces changes in the levels of neurotransmitter amino acids in male rat brain regions

Abstract: Context:Nigella sativa L. (Ranunculaceae) (NS) has been used for medicinal and culinary purposes. Different parts of the plant are used to treat many disorders.Objective: This study investigates the effects of NS methanol extract on brain neurotransmitter amino acid levels.Materials and methods: We measured the changes in aspartate, glutamate, glycine and γ-aminobutyric acid in five brain regions of male Wistar rats after methanol extract treatment. Animals were injected intraperitoneally with saline solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…The plants are mainly consumed for their seeds and seed oil, as commented before. The main constituents of N. sativa seeds reported in the literature are fixed oil (27–40%), proteins (16–19%), characterized mainly by the amino acids arginine, glutamic acid, leucine, lysine; minerals (1.79–3.74%), like Cu, Zn, P, and Fe; carbohydrates (28.5–33.7%), and solubre dietary fibers (5.5–8.9%) ( Al-Naqeep et al, 2009 ; Tiruppur Venkatachallam et al, 2010 ; Kooti et al, 2016 ; El-Naggar et al, 2017 ; Saxena et al, 2017 ). Concerning the phytochemical composition of Nigella seeds, the most interesting plant part, it is constituted of alkaloids, terpenes and phenolic compounds ( Agradi et al, 2001 ).…”
Section: Phytoconstituentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The plants are mainly consumed for their seeds and seed oil, as commented before. The main constituents of N. sativa seeds reported in the literature are fixed oil (27–40%), proteins (16–19%), characterized mainly by the amino acids arginine, glutamic acid, leucine, lysine; minerals (1.79–3.74%), like Cu, Zn, P, and Fe; carbohydrates (28.5–33.7%), and solubre dietary fibers (5.5–8.9%) ( Al-Naqeep et al, 2009 ; Tiruppur Venkatachallam et al, 2010 ; Kooti et al, 2016 ; El-Naggar et al, 2017 ; Saxena et al, 2017 ). Concerning the phytochemical composition of Nigella seeds, the most interesting plant part, it is constituted of alkaloids, terpenes and phenolic compounds ( Agradi et al, 2001 ).…”
Section: Phytoconstituentsmentioning
confidence: 99%
“…The oil of N. sativa seeds has been highly studied, showing predominance of linoleic acid (1) (50–60%), oleic acid (2) (20%), myristic acid (3) (30%), and palmitic acid (4) (12.5%) ( Tiruppur Venkatachallam et al, 2010 ; Kooti et al, 2016 ; El-Naggar et al, 2017 ; Saxena et al, 2017 ) ( Figure 1 ). Nigella seed oil from Morocco also showed that the major fatty acids were linoleic acid (1) (58.5 and 56.5%), oleic acid (2) (23.8 and 24.9%) and palmitic acid (4) (13.1 and 11.9%) using cold press and solvent extraction, respectively ( Gharby et al, 2015 ).…”
Section: Phytoconstituentsmentioning
confidence: 99%
See 1 more Smart Citation
“…[12] It also corroborates earlier reports on the neuro-pharmacological potentials of Nigella sativa. [13] Furthermore, a positive discrimination index indicates a higher novel object recognition memory. The ETH group had a discrimination index of -0.1, indicating a lower recognition memory as a result of the prenatal ethanol exposure, while the NSE group had the highest discrimination index in corroboration of the prophylactic effect of maternal pregestational exposure to Nigella sativa on the NSE pups.…”
Section: Discussionmentioning
confidence: 99%
“…Six male albino rats (Rattus norvegicus) weighting 200 -300 g (from Department of Biology, College of Science, University of Zakho) were recruited for the current study. Prior to start the experiment, the animals were placed under standard laboratory conditions (22±2ºC and free access to water and libitum with a 12 hrs on light/12 hrs off light) (17). Standard pellets comprising 25.6 % soya, 1.5 % lime stone, 4.4 % oil, 0.63 % salt, 0.062 % choline chloride, 0.158 % methionine, 66.6 % wheat and 0.05 % trace elements were given to the animals (18).…”
Section: Ratsmentioning
confidence: 99%